Highly efficient and recyclable water-soluble fullerene-supported PdCl2 nanocatalyst in Suzuki–Miyaura cross-coupling reaction. Issue 43 (4th July 2018) - Li, Jingbo; Huo, Ping; Zheng, Junwei; Zhou, Xiuming; Liu, Wanyun
Abstract : The water-soluble fullerene-supported PdCl2 nanocatalyst [C60 -TEGS /PdCl2 ] exhibits high activity and recycling in pure water toward the Suzuki–Miyaura cross-coupling reaction. Abstract : A water-soluble fullerene-supported PdCl2 nanocatalyst [C60 -TEGS /PdCl2 ] was prepared by coordination of water-soluble fullerene nanoparticles with palladium chloride. In pure water, the catalytic activity of nanocatalyst [C60 -TEGS /PdCl2 ] for Suzuki–Miyaura cross-coupling reaction was investigated under different reaction conditions. The results showed that biphenyl compounds could be synthesized in high yields at room temperature using 0.01 mol% of [C60 -TEGS /PdCl2 ] as the catalyst and K2 CO3 as the base with the reaction time of 4 h. The catalyst was recycled five times, and the yield clearly did not decrease.